Chemical constituents and biological activities of scaph/ummacropodum (miq.) beumee and sap/umbaccatum (roxb.) / Laode Muhammad Ramadhan Al Muqarrabun - Al Muqarrabun, Laode Muhammad Ramadhan (2014)
The stem barks of Scaphium macropodum, known as Kembang Semangkuk Jantung (Malay), and Sapium baccatum, known as Ludai (Malay), have been investigated for their phytochemical and pharmacological properties. Several chromatographic techniques were used to separate the chemical compounds including Vacuum Liquid Chromatography (VLC), Radial Chromatography (Rf') and Column Chromatography (CC). A new sesquiterpene named malayscaphiol (8M4) along with two lupane triterpenes, lupeol (8Ml) and lupenone (8M2) and stigmasterol (SM3), were successfully isolated from the stem bark of S. macropodum, while a new triterp ene, malaytaraxcrate (8B3), along with two oleanane triterpenes, taraxerol (SBl) and taraxerone (882), docosyl trans-isoferulate (8B4) and docosanoic acid-2',3'dihydroxypropyl ester (8B5) were identified from the stem bark of S. baccatum. The structures of the compounds were determined using several spectroscopic methods, i.e. mass spectrometry (MS), UV-Vis, FT-IR, 10 and 2D NMR including HMQC, HMBC, COSY and NOESY. Several isolated compounds were subjected to cytotoxicity and anti-cholinesterase (anti- AChE) assays to identify their biological properties. Six compounds i.e. 8Ml, 8M2, 8M3, 8B2, 8B4 and SB5 were subjected to cytotoxicity assay. All the tested compounds demonstrated weak anti-cancer activity against HT-29 and MDA-MB cell lines, with SMI and 8M2 exhibited the strongest cytotoxicity among the tested compounds against HT-29 and MDA-MB, respectively. Only 8Ml showed toxic effect towards normal cell line (3T3) with ICso of 38.92 ug/ml., For anti-AChE assay, three compounds were tested i.e. SMl, SM2 and SB2. All the tested compounds exhibited insignificant anti-AChE activity at concentration of 1000 ug/ml., The ICso of the tested compounds could not be determined, because there was only one data point available in this test. Their antiAChE activity were significantly lower than the standard tacrine (ICso== 25 ug/ml.),